When you solved that put in x=1 and y=0 to find a value for the constant of integration, C
Okay, so I get (y-3)^2=C(1)e^((-1/3)cos3x) Then plug in x=1 and y=0 to get C. 9=C(1)(.7168) So C(1)=12.5558? So then I plug it back into the equation to get:
Okay, so I get (y-3)^2=C(1)e^((-1/3)cos3x) Then plug in x=1 and y=0 to get C. 9=C(1)(.7168) So C(1)=12.5558? So then I plug it back into the equation to get:
(y-3)^2=12.5558e^((-1/3)cos3x)?
Where did you get the exponential from?
As u = y-3:
The RHS is a standard trig integral, pull out the 1/3 to get it as